Role of the cGAS/STING pathway in the control of Brucella abortus infection acquired through the respiratory route - Alonso Paiva, Iván M.; A. Santos, Raiany; Brito, Camila B.; Ferrero, Mariana C.; Ortiz Wilczyñski, Juan Manuel; Silva, Eugenio A. Carrera; C. Oliveira, Sergio; Baldi, Pablo C. (Frontiers in Immunology, 2023)
Despite the importance of the respiratory route for Brucella transmission, the lung immune response to this pathogen is scarcely characterized. We investigated the role of the STING/cGAS pathway of microbial DNA recognition in the control of respiratory Brucella infection. After in vitro B. abortus infection, CFU numbers were significantly higher in alveolar macrophages (AM) and lung explants from STING KO mice than in samples from wild type (WT) mice, but no difference was observed for cGAS KO samples. CFU were also increased in WT AM and lung epithelial cells preincubated with the STING inhibitor H151. Several proinflammatory cytokines (TNF-α, IL-1β, IL-6, IP-10/CXCL10) were diminished in Brucella-infected lung explants and/or AM from STING KO mice and cGAS KO mice. These cytokines were also reduced in infected AM and lung epithelial cells pretreated with H151. After intratracheal infection with B. abortus, STING KO mice exhibited increased CFU in lungs, spleen and liver, a reduced expression of IFN-β mRNA in lungs and spleen, and reduced levels of proinflammatory cytokines and chemokines in bronchoalveolar lavage fluid (BALF) and lung homogenates. Increased lung CFU and reduced BALF cytokines were also observed in cGAS KO mice. In summary, the STING/cGAS pathway induces the production of proinflammatory cytokines after respiratory Brucella infection, which may contribute to the STING-dependent control of airborne brucellosis.